Comparison of three treatment protocols with intra-articular low or intermediate molecular weight hyaluronic acid in early symptomatic knee osteoarthritis - Felice Galluccio; Daniela D’Angela; Barbara Polistena; Francesco Porta; Tatiana Barskova; Lorenzo Tofani; Federico Spandonaro; Marco Matucci-Cerinic (Therapeutic Advances in Musculoskeletal Disease, 2021)
Introduction: Viscosupplementation with hyaluronic acid (HA) is indicated for non-responders to non-pharmacological therapy, to analgesics or when non-steroidal anti-inflammatory drugs (NSAIDs) are contraindicated. The aim of this study is to compare the efficacy, safety and costs of three different HA treatments ( Sinovial® Forte , sinovial one and hyalgan). Patients and methods: Ninety patients with grade I/II Kellgren–Lawrence knee osteoarthritis were included in three groups, the first was treated with hyalgan (weekly for 5 weeks), the second with Sinovial® Forte (weekly for 3 weeks) and the third group with a single injection of sinovial one. Results: All three treatments were effective, with an average reduction in the Western Ontario and McMaster Universities osteoarthritis index (WOMAC) score of 18.9 points for hyalgan, 18.04 points for Sinovial® Forte and 17.92 points for sinovial one. The comparison of the three groups did not show any statistical difference in terms of efficacy. National health system (NHS) and social costs are, respectively, €419.12 and €853.43 for hyalgan, €338.64 and €599.22 for Sinovial® Forte , €221.56 and €308.42 for sinovial one. Conclusion: All three treatments were equally effective with no statistically significant differences; thus, the treatment with sinovial one may be considered as clinically effective as the other two regimens, but with a very efficient cost profile in early symptomatic knee osteoarthritis.